Electoral cycles in macroprudential regulation - Karsten Müller (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2019)
Do politics matter for macroprudential policy? I show that changes to macroprudential regulation exhibit a predictable electoral cycle in the run-up to 221 elections across 58 countries from 2000 through 2014. Policies restricting mortgages and consumer credit are systematically less likely to be tightened before elections during credit booms and economic expansions. Consistent with theories of opportunistic political cycles, this pattern is stronger when election outcomes are uncertain or in countries where political interference is more likely. In contrast to monetary policy, I find limited evidence that central banks are uniquely insulated from political cycles in macroprudential policy. These results suggest that political pressures may limit the ability of regulators to "lean against the wind."
Keywords: G18; G21; G28; D72; D73; P16; 330; macroprudential regulation; electoral cycles; regulatory cycles; political economy; central bank independence